Changes in the expression profiles of claudins during gonocyte differentiation and in seminomas. (20th November 2015) - Manku, G.; Hueso, A.; Brimo, F.; Chan, P.; Gonzalez‐Peramato, P.; Jabado, N.; Gayden, T.; Bourgey, M.; Riazalhosseini, Y.; Culty, M.
Summary: Testicular germ cell tumors (TGCTs) are the most common type of cancer in young men and their incidence has been steadily increasing for the past decades. TGCTs and their precursor carcinoma in situ (CIS) are thought to arise from the deficient differentiation of gonocytes, precursors of spermatogonial stem cells. However, the mechanisms relating failed gonocyte differentiation to CIS formation remain unknown. The goal of this study was to uncover genes regulated during gonocyte development that would show abnormal patterns of expression in testicular tumors, as prospective links between failed gonocyte development and TGCT. To identify common gene and protein signatures between gonocytes and seminomas, we first performed gene expression analyses of transitional rat gonocytes, spermatogonia, human normal testicular, and TGCT specimens. Gene expression arrays, pathway analysis, and quantitative real‐time PCR analysis identified cell adhesion molecules as a functional gene category including genes downregulated during gonocyte differentiation and highly expressed in seminomas. In particular, the mRNA and protein expressions of claudins 6 and 7 were found to decrease during gonocyte transition to spermatogonia, and to be abnormally elevated in seminomas. The dynamic changes in these genes suggest that they may play important physiological roles during gonocyte development. Moreover, our findings support the idea that TGCTs arise from a disruption of gonocyte differentiation, and position claudins as interesting genes to further study in relation to testicular cancer.